Study of the effect of the application of the double finish drawing die on the plastic properties of steel high carbon wire - V. A. Evdonich; Yu. L. Bobarikin; Yu. V. Martianov; T. A. Akhmetov (Литьë и металлургия, 2019)
The possibility of application of the double finishing drawing die at the stage of fine-drawing in the manufacture of steel metal cord 2x0 30SHT is сontemplated. As a result of the performed studies, a numerical finite element model of wire drawing in a serial finishing single fiber and in an experimental double finishing fiber has been developed. The obtained distribution of effective plastic deformation in the wire during drawing shows that when drawing in a double fiber, there is a higher uniformity of deformation in the direction of the radius of the wire along the cross section located at the outlet of the die. The distribution of effective stresses in the wire when drawing shows that when drawing in a double fiber, there is a more uniform distribution of effective stresses in the direction of the radius of the wire along the cross section located at the outlet of the die.Further experimental tests performed at the drawing mill NT 12.4 in StPC-1 showed that the use of double dies allowed to increase the plastic properties of the wire 0.30 SHT, manifested in technological tests by increasing the number of reversible twists of the wire from 7 to 78 and reducing the ratio of yield strength to tensile strength decreased from 95 to 91.